KAJIAN HUKUM MENGENAI TATA KELOLA TANAH DI DESA ALINDAU, KECAMATAN SINDUE TOBATA - Silviana, Giska; Datupalinge, Suarlan; Kemalasari, Dewi (Jurnal Ilmu Hukum Lasadindi, 2025)
Land is a natural resource of strategic value for the livelihood of the Indonesian people and plays an essential role in national and regional development. In the context of land law, the state holds the authority to regulate the use and management of land for the greatest prosperity of the people, as mandated in Article 33 paragraph (3) of the 1945 Constitution and further elaborated in Law No. 5 of 1960 concerning the Basic Agrarian Law (UUPA). One of the recurring issues in practice is the management of village land, particularly land categorized as tanah kas desa (village treasury land). This study employs an empirical juridical method with the objective of analyzing the legal status and dispute resolution concerning village land controlled by residents in Alindau Village, Sindue Tobata District.The findings reveal that the village land in Alindau has become the object of dispute between the village government and residents who occupy and use the land without a clear legal basis. The problem arises mainly due to the absence of written agreements on land management and weak village asset administration. From a regulatory perspective, the core issue lies in the ambiguity of the definition, classification, and legal status of village land, which leads to confusion between village land and village treasury land. The dispute resolution efforts undertaken by the village government through non-litigation approaches (deliberation) have not produced satisfactory results, as the occupants refused to return the land. Based on the study, the dispute should be resolved through litigation processes to ensure legal certainty and protection of village assets.This research highlights the need for land law reform at the village level through the strengthening of regulations, administrative improvement of village assets, and capacity building for village officials in land management to prevent similar conflicts in the future